Pro-social 50-kHz ultrasonic communication in rats: post-weaning but not post-adolescent social isolation leads to social impairments—phenotypic rescue by re-socialization - Seffer, Dominik; Rippberger, Henrike; Schwarting, Rainer K. W.; Wöhr, Markus (Frontiers in Behavioral Neuroscience, 2015)
Rats are highly social animals and social play during adolescence has an important role for social development, hence post-weaning social isolation is widely used to study the adverse effects of juvenile social deprivation and to induce behavioral phenotypes relevant to neuropsychiatric disorders, like schizophrenia. Communication is an important component of the rat’s social behavior repertoire, with ultrasonic vocalizations (USV) serving as situation-dependent affective signals. High-frequency 50-kHz USV occur in appetitive situations and induce approach behavior, supporting the notion that they serve as social contact calls; however, post-weaning isolation effects on the behavioral changes displayed by the receiver in response to USV have yet to be studied. We therefore investigated the impact of post-weaning isolation on socio-affective information processing as assessed by means of our established 50-kHz USV radial maze playback paradigm. We showed that post-weaning social isolation specifically affected the behavioral response to playback of pro-social 50-kHz but not alarm 22-kHz USV. While group-housed rats showed the expected preference, i.e. approach, towards 50-kHz USV, the response was even stronger in short-term isolated rats (i.e. 1 day), possibly due to a higher level of social motivation. In contrast, no approach was observed in long-term isolated rats (i.e. 4 weeks). Importantly, deficits in approach were reversed by peer-mediated re-socialization and could not be observed after post-adolescent social isolation, indicating a critical period for social development during adolescence. Together, these results highlight the importance of social experience for affiliative behavior, suggesting a critical involvement of play behavior on socio-affective information processing in rats.